Electronic Invoicing Reform and Corporate Disclosure Quality in the Egyptian Capital Market - Youssef Ahmed Hassan; Mariam Khaled El Sayed; Omar Mahmoud Ibrahim; Salma Tarek Mostafa (Journal of Economics Business Industry, 2025)
As a foundational pillar of capital market development, corporate information disclosure quality plays a central role in directing financial resources toward productive economic activities. This study treats Egypt's national electronic invoicing system, established by the Egyptian Tax Authority in December 2020, as a quasi-natural experiment and examines its effect on the information disclosure quality of non-financial companies listed on the Egyptian Exchange and headquartered in Cairo, using panel data from 2016 to 2024 and the difference-in-differences methodology. Results show that the introduction of digital transaction infrastructure significantly improves corporate information disclosure quality, and this finding remains stable across a series of robustness checks. Mechanism analysis reveals that financial bill digitization reduces corporate financial risk and strengthens internal control effectiveness, both serving as channels through which disclosure quality improves. Further heterogeneity analysis shows that the effect is more pronounced among firms facing higher internal governance difficulty and stronger external governance intensity. Improved disclosure quality is also associated with higher long-term and short-term firm value. The findings contribute to the literature on digital financial infrastructure and capital market quality in emerging economies, and provide empirical evidence for policy efforts aimed at modernizing Egypt's multilevel financial system.